Wanopvattings by biologie-onderwysers ten opsigte van eenheidstemas in biologie-onderwys (2014)
M.Ed. === This study focuses on the misconceptions that exist among teachers in the field of unifying themes in Biology teaching. The researcher feels confident that teachers are well underlain in their field of study, and that meaningful teaching occurs in Biology classes. His concern is that the fundamental unifying themes in Biology that enables pupils to reach higher cognitive levels of thought, are not utilised fully in pupils and teachers, learning and training. Investigations of these phenomena are being done through misconceptions that may occur at teachers of Biology. This forms the main aim of the study. The researcher feels that the fewer misconceptions' teachers have, the better students will be taught. Qualitative and quantitative research methods are being used to maximise the research effectiveness. Trough these methods the researcher found that teachers are well underlain in their studies but lack utilisation of unifying themes in the learning environment. Teachers concentrate on one or two themes, ignoring the remainder. The researcher hopes to make a meaningful contribution to the teaching of Biology as well as to improve the quality of teacher training programs in Biology didactic courses through awareness of these phenomena.